Human rights and empowerment - Rahman, Mizanur, 1956-; Empowerment Through Law of the Common People (Project); Human Rights Summer School & Community Law Reform (Project) (Dhaka, Bangladesh : Empowerment Through Law of the Common People, 2001)
With reference to Bangladesh; contributed articles.
"Human Rights Summer School, 2001."
Includes bibliographical references.
Keywords: Human rights -- Social aspects; Social legislation; Civil rights -- Bangladesh